EVALUASI PELAKSANAAN PROGRAM PRAKTEK KERJA INDUSTRI SISWA KELAS XI DI SMK NEGERI 3 PAYAKUMBUH TAHUN AJARAN 2017/2018 - zi, fauziah; Hakiki, Muhammad; Putra, Yogi Irdes; Ridoh, Ahmad (Information Technology Education Department, 2020)
This study aims to evaluate the implementation of work practices Industry SMK N 3 Payakumbuh. The evaluation of the work practices of the industry (Prakerin) viewed from component design, Installation, and Cost, Product Procces faced in implementing Prakerin. Research results show that implementation of work practices in the industry of SMK N 3 Payakumbuh Computer Network Engineering program as a whole include: (1) evaluation of Goal Indicators of program design: prakerin acquire standard score 81.5% good. Then for the Preparatory Program indicators Prakerin earn standard scores 80.25%. (2) evaluation of Installation: indicator of the readiness of Teachers Supervising earn standard scores 85.33% good. then the instructor Readiness for DU/received 73% of the score is pretty standard. Next on the supporting facilities and infrastructure indicators obtained standard score 82% good. Next on the indicators of Source Funds obtain standard scores 83.33% good. Next on the relevance of the indicator Program with the needs of the Students acquire standard score 80,53% good. (3) the evaluation Process: preparation of Indicators gained 85.6% score is stdandar good. indicators for Program execution then Prakerin gained 75.83% score is fairly standard. (4) the evaluation of the Product: Indicators of Learning Assessment Participants Prakerin gained 69.75% score is fairly standard